Surveillance, Architecture and Control
XVII, 335 p. 17 illus., 15 illus. in color.
Keywords: This edited collection examines the culture of surveillance as it is expressed in the built environment. Expanding on discussions from previous collections; Spaces of Surveillance: States and Selves (2017) and Surveillance, Race, Culture (2018), this book seeks to explore instances of surveillance within and around specific architectural entities, both historical and fictitious, buildings with specific social purposes and those existing in fiction, film, photography, performance and art. Providing new readings of, and expanding on Foucault’s work on the panopticon, these essays examine the role of surveillance via disparate fields of enquiry, such as the humanities, social sciences, technological studies, design and environmental disciplines. Surveillance, Architecture and Control seeks to engender new debates about the nature of the surveilled environment through detailed analyses of architectural structures and spaces; examining how cultural, geographical and built space buttress and produce power relations. The various essays address the ongoing fascination with contemporary notions of surveillance and control.